PENGARUH KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PT IMPACT CREDIT SOLUTIONS - Chairun Nisa; A Sigit Pramono Hadi (Jurnal Komunikasi, 2025)
Organizations need an active communication touch to foster community participation. All of these communication activities are an integral part that cannot be separated from an institution or organization. Organizational Communication has an important role in understanding the behavior of each employee, the company pays attention to all aspects that can affect employee performance. Communication within the company has not run optimally, there are many misunderstandings between fellow employees and delays in receiving information resulted in the performance of ICS employees in the first quarter experiencing a decline and can be said to be unsatisfactory. This study aims to determine the effect of organizational communication on the performance of PT Impact Credit Solutions employees. The theory used in this study is the theory of organizational communication according to Pace and Faules and employee performance from Mathis and Jackson. This research is a quantitative research, the method used in order to collect data using a survey, the sampling technique is saturated sampling. The sample studied was 40 people. The analytical method used in this study is statistical analysis and the SPSS program is used for processing. The results showed that there was a moderate influence between organizational communication variables (X) and employee performance variables (Y).